2006
DOI: 10.1097/01.psy.0000232270.78071.28
|View full text |Cite
|
Sign up to set email alerts
|

Selective Processing of Gastrointestinal Symptom-related Stimuli in Irritable Bowel Syndrome

Abstract: These results indicate that IBS patients selectively process gastrointestinal symptom-related words compared with neutral words when they are presented subliminally but not when they are presented supraliminally. In contrast, healthy controls demonstrate the opposite pattern. Implications for the cognitive mechanisms in IBS, and future research directions, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…However, objective measures of attention to health-related stimuli have yielded less consistent findings. For symbolic material (e.g., illness words), some studies have found increased interference on the emotional Stroop task in patients with MUS (e.g., Afzal et al, 2006;Lim and Kim, 2005;Witthöft et al, 2006). These effects may be attributable to increased avoidance of health-threat rather than engagement with it (De Ruiter and Brosschot, 1994), however, or stimulus negativity more generally (Posserud et al, 2009).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 96%
“…However, objective measures of attention to health-related stimuli have yielded less consistent findings. For symbolic material (e.g., illness words), some studies have found increased interference on the emotional Stroop task in patients with MUS (e.g., Afzal et al, 2006;Lim and Kim, 2005;Witthöft et al, 2006). These effects may be attributable to increased avoidance of health-threat rather than engagement with it (De Ruiter and Brosschot, 1994), however, or stimulus negativity more generally (Posserud et al, 2009).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 96%
“…Some studies have found that MUS patients attend more to illness-relevant stimuli than controls [23][24][25], although this has proved difficult to replicate [26][27][28][29][30]. In terms of more direct measures of body-focused attention, one study found that high SSAS scorers were poorer than low scorers at detecting physiological events (heartbeats), suggesting an attentional deficit in the former [31]; two other studies have found no relationship between SSAS scores and heartbeat detection, however [32,33].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, a large number of studies found that patients with MUSs and people suffering from common HCs also show increased selective attention for external information related to their HCs, including pain (for reviews, see Refs. [8,11,12]). Likewise, several studies have linked symptom reporting with increased attention to SEN [13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%